Composite coatings of S-HA nanoparticles and Schiff base on ZE21B alloy for stronger corrosion resistance and biological performance - Zhonghua Xue; Xiaojing Sun; Hang Li; Mujahid Iqbal; Liujie Qi; Fei Wang; Yachen Hou; Jingan Li; Shaokang Guan (Journal of Magnesium and Alloys)
In order to prolong the service time and enhance the biocompatibility of magnesium (Mg) alloys used for cardiovascular scaffolds, the composite coatings of Schiff base (corrosion inhibitor) and sulfonated hyaluronic acid (S-HA) nanoparticles (NP@S-HA) with different sulfur content (10.02 wt% and 11.55wt%) were prepared on ZE21B alloy by means of electrostatic spraying with spraying time of 0.5 min, 1.0 min and 1.5 min in this paper. Through a series of representations including corrosion experiments and biological characterization, the composite coatings with a sulfur content of 11.55wt% and a spray time of 1.0 min were finally picked due to its better comprehensive performances, which provides a new possibility for the surface modification of degradable Mg alloy cardiovascular scaffolds.